Effekt von Ausdauer- und Krafttraining auf hämodynamische Parameter und Herzfrequenzvariabilität - Missal, P.; Ketelhut, R. G. (Herzfrequenzvariabilität: Methoden und Anwendungen in der Sportwissenschaft, Arbeits- und Intensivmedizin sowie Kardiologie. 7. Internationales HRV-Symposium am 4. März 2017 in Halle (Saale), 2018)
Regular physical activity is known to have a positive influence on cardiac structure and cardiovascular function. Registration of heart rate variability (HRV) provides a sensitive non-invasive evaluation of cardiac autonomic control. Hemodynamic parameters reflect alterations in cardiovascular function and structure. The present study was designed to compare the influence of a moderate aerobic training and a strength training on both HRV and peripheral and central hemodynamics.